Improvement of Charge Characteristics of Oxisols Using Basalt and Rice Husk Compost for Cocoa Growth - Anda, Markus (2006)
One of the major limiting factors of Oxisols for agricultural crop production is a very low negative charge, leading to deficiency of base cations imparted by leaching. This condition is exacerbated by the low pH and high Al saturation. Basalt is naturally available and well known as parent material of fertile and highly productive soils, whereas rice husk is an agro-waste that can cause serious environmental problems , which on the other hand, is a highly valuable material if used as a soil amendment. The general objective of this study was to assess charge characteristics of Oxisols and restore their productivity by generating surface negative charge and increasing nutrient content using basalt and rice husk compost for cocoa growth.